2021
DOI: 10.7573/dic.2020-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Paediatrics: how to manage obstructive sleep apnoea syndrome

Abstract: Obstructive sleep apnoea syndrome (OSAS) is defined as the intermittent reduction or cessation of airflow due to partial or complete obstruction of the upper airway during sleep. Paediatric OSAS has specific contributing factors, presenting symptoms and management strategies in various age groups. Untreated OSAS can lead to detrimental effects on neurocognitive development and cardiovascular and metabolic functions of a growing child. In the past decade, practice guidelines have been developed to guide the eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 128 publications
0
16
0
1
Order By: Relevance
“…Adenotonsillectomy improves snoring, OSA, enuresis, behavior, and growth, according to numerous research. Surgery is the chosen course of treatment for moderate to severe juvenile adenoid and/or tonsil hypertrophy when the results of endoscopic examination or evaluation of the upper airway (including the nose, nasopharynx, oropharynx, laryngopharynx, and larynx) are consistent with the condition OSA (according to the 2012 American Academy of Pediatric guidelines) [25][26][27][28][29]. The evaluation of surgical indications should also take into account the child's symptoms and the expectations of the parents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adenotonsillectomy improves snoring, OSA, enuresis, behavior, and growth, according to numerous research. Surgery is the chosen course of treatment for moderate to severe juvenile adenoid and/or tonsil hypertrophy when the results of endoscopic examination or evaluation of the upper airway (including the nose, nasopharynx, oropharynx, laryngopharynx, and larynx) are consistent with the condition OSA (according to the 2012 American Academy of Pediatric guidelines) [25][26][27][28][29]. The evaluation of surgical indications should also take into account the child's symptoms and the expectations of the parents.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to fully explain to them the realistic expectations for surgical outcomes as a result. It's also crucial to be ready for any Anesthesia-related complications, postoperative respiratory failure, hemorrhage, velopharyngeal insufficiency, nasopharyngeal stenosis, pain, and dehydration are examples of perioperative problems [25,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, children with primary snoring are not routinely recommended for adenotonsillar surgery, the first‐line treatment for paediatric obstructive sleep apnoea, which has been shown to improve cardiovascular outcomes in children 7 . Other less invasive treatments such as nasal steroids have been shown to improve milder disease 8 and may provide cardiovascular benefits to snoring children. It is important that children are treated as early as possible as studies have shown that both the cardiovascular 9 and neurocognitive 10 sequelae are less severe in pre‐school compared to school‐aged children.…”
mentioning
confidence: 99%
“…Se utilizan también como tratamiento de la rinitis (126) . Por lo cual, los corticosteroides nasales tales como la budesónida, la fluticasona y la mometasona podrían utilizarse comúnmente en el tratamiento de los TRS pediátricos, pero existen pocos ensayos controlados de alta calidad disponibles (127) .…”
Section: Corticosteroides Nasalesunclassified